2019
DOI: 10.3389/fphy.2018.00154
|View full text |Cite
|
Sign up to set email alerts
|

A Nonequilibrium-Potential Approach to Competition in Neural Populations

Abstract: Energy landscapes are a useful aid for the understanding of dynamical systems, and a valuable tool for their analysis. For a broad class of rate models of neural networks, we derive a global Lyapunov function which provides an energy landscape without any symmetry constraint. This newly obtained "nonequilibrium potential" (NEP) predicts with high accuracy the outcomes of the dynamics in the globally stable cases studied here. Common features of the models in this class are bistability-with implications for wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…We have studied the effect of coupling between units and sought the optimal configuration (number N of coupled units) in order to enhance the system's energy harvesting. In agreement with [23], whilst diffusive coupling between units reduces the system's performance, anti-diffusive couplings cause an enhancement. Next we found that it does so via the mechanism of a diffusive instability.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…We have studied the effect of coupling between units and sought the optimal configuration (number N of coupled units) in order to enhance the system's energy harvesting. In agreement with [23], whilst diffusive coupling between units reduces the system's performance, anti-diffusive couplings cause an enhancement. Next we found that it does so via the mechanism of a diffusive instability.…”
Section: Discussionsupporting
confidence: 70%
“…After confirming our preliminary evidence [23] that the performance of antidiffusively coupled units can be notably enhanced as compared with the non-coupled case, we ask ourselves what the optimal number N of (antidiffusively) coupled units is. For our surprise however (see Fig.…”
Section: Number Of Unitsmentioning
confidence: 72%
See 2 more Smart Citations
“…Among its virtues, it yields a visual criterion for the EW-KPZ crossover. (2) The Wilson-Cowan model of the neocortex-describing the competition between excitatory and inhibitory neural populations-is generically a non-relaxational potential system admitting a bona-fide NEP [63]. In Section 4, we illustrate the usefulness of the NEP concept to draw results on stochastic thermodynamics by deriving a Jarzynski equality [64] in the Wilson-Cowan model and a thermodynamic uncertainty relation (TUR) [65] in the KPZ equation.…”
Section: Introductionmentioning
confidence: 99%